The Subject-Verb Agreement Errors on Students’ Writing - Vitri Angraini Hardi; Lusi Marleni; Nurhidayah Sari (Journal of English Language and Education, 2022)
Subject-verb agreement is an essential component to be mastered by English Language Learners to produce a good writing. Examining the students’ errors on writing is part of the evaluation in English language learning and teaching. To produce a good writing, the English language learners have to be able to know the rules of the language use. However, the English learners still struggle in mastering the subject-verb agreement in the writing. Due to the reason, it would be significant to diagnose the errors made by the students as well as to explore the factors contribute the errors. To obtain the data, the researcher employed a document analysis and a semi-structure interview. The findings showed most of the errors belonged to misinformation category (33%) and were subsequently followed by omission category (29%) and addition category (29%) and misformation (9%). In addition, from the interview the researcher also found three major factors contribute the students’ errors, namely ignorance the editing process, the unawareness of the grammar rules, and intralingual errors.